A Safe Practice Standard for Barcode Technology. Issue 2 (June 2015) - Leung, Alexander A.; Denham, Charles R.; Gandhi, Tejal K.; Bane, Anne; Churchill, William W.; Bates, David W.; Poon, Eric G.
Abstract : Objective: Safety advocates have identified barcode verification technology as an important tool to improve health-care practices. Methods: We evaluated the evidence for the role of barcode technology in improving a wide range of medication safety outcomes across a broad range of settings. Important implementation issues were highlighted to guide standards for the safe adoption of barcode technology. Results: Adverse drug events are common, occurring frequently in both inpatient and outpatient settings. Although approximately half of all preventable adverse drug events in inpatients result from medication errors arising from transcription, dispensing, and administration, these errors are far less likely to be caught than in any of the earlier stages of the medication use process and are therefore most amenable to improvement. When integrated with electronic medication administration records, barcode systems are associated with complete elimination of transcription errors. Furthermore, barcode-assisted dispensing systems are associated with 93% to 96% reductions in dispensing errors, and 85% reductions in potential adverse drug events in dispensing. Most studies have reported large and significant reductions in administration errors by up to 80% after implementation of barcode medication administration systems. Although most studies of barcode technology have been conducted in the adult inpatient setting, the limited data available also support their benefit in pediatric and outpatient settings. Conclusions: There is growing evidence for the efficacy of barcode solutions in improving overall medication safety. Standards for the implementation of barcode technology are proposed.